2018
DOI: 10.3382/ps/pey037
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and activity of methionine converting enzymes in broiler chickens fed methionine isomers or precursors

Abstract: Common dietary supplemental methionine (Met) sources include DL-methionine (DL-Met) and the Met precursor DL-2-hydroxy-4-(methylthio) butanoic acid (DL-HMTBA). For bio-utilization, D-Met and DL-HMTBA are converted into L-Met through oxidation and transamination. The objective of this study was to determine the effect of different dietary supplemental Met sources on gene expression and enzyme activity of Met oxidases in male broiler chickens. Liver, muscle, duodenum, jejunum, and ileum were collected at days 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…In contrast to our expectations, the Met source neither affected anabolic nor catabolic pathways in the muscle on the molecular level. This may be explained by the observation that D‐ and L‐HMTBA are converted to L‐Met after absorption primarily in tissues other than the muscle (Martín‐Venegas, Geraert, & Ferrer, ; Zhang, Gilbert, Noonan, Saremi, & Wong, ), thus whatever the dietary Met source, muscle cells will receive primarily L‐Met. In contrast, when D‐Met or DL‐HMTBA were directly supplied to cell types likes myoblasts in an earlier in vitro study significant effects were observed on anabolic pathways compared to cells supplied L‐Met (Métayer‐Coustard et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast to our expectations, the Met source neither affected anabolic nor catabolic pathways in the muscle on the molecular level. This may be explained by the observation that D‐ and L‐HMTBA are converted to L‐Met after absorption primarily in tissues other than the muscle (Martín‐Venegas, Geraert, & Ferrer, ; Zhang, Gilbert, Noonan, Saremi, & Wong, ), thus whatever the dietary Met source, muscle cells will receive primarily L‐Met. In contrast, when D‐Met or DL‐HMTBA were directly supplied to cell types likes myoblasts in an earlier in vitro study significant effects were observed on anabolic pathways compared to cells supplied L‐Met (Métayer‐Coustard et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, when D‐Met or DL‐HMTBA were directly supplied to cell types likes myoblasts in an earlier in vitro study significant effects were observed on anabolic pathways compared to cells supplied L‐Met (Métayer‐Coustard et al, ). This may indicate these cell types are either unable or only partly able to convert these Met sources to L‐Met (Martín‐Venegas et al, ; Zhang, Gilbert, et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The D-isomer of DL-Met is first converted in liver and kidney by d-amino-oxidase into 2-keto-4 (methylthio) butanoic acid (KMB) and then by transamination into L-Met. MHA, on the other hand, has to be oxidized to KMB in two different enzymatic systems: first by L-2-hydroxy acid oxidase (L-HAOX; mainly located in hepatic and renal peroxisomes) and by D-2-hydroxy acid dehydrogenase (D-HADH; in the mitochondria of various tissues) [26,34,35,36].…”
Section: Introductionmentioning
confidence: 99%